Classic home video games, 1989-1990 : a complete guide to Sega Genesis, Neo Geo and TurboGrafx-16 games - Weiss, Brett, 1967- (McFarland & Company, Inc. Publishers, 2011)
"The third in a series about home video games, this detailed reference work features descriptions and reviews of every official U.S.-released game for the Neo Geo, Sega Genesis and TurboGrafx-16. Organized alphabetically by console brand, each chapter includes a description of the game system, followed by substantive entries for every game released for that console"--Provided by publisher